Influence of curing mode of resin luting cements on bond strength to dentin - Marcelo Giannini; Andreia Assis Carvalho; Ariovaldo Stefani; Wladimir Franco de Sá Barbosa; Lawrence Gonzaga Lopes (Universidade Estadual de Campinas, 2017)
Self-adhesive, dual-polymerizing resin cements require no treatment to the prepared tooth surfaces before cementation. Aim: The aim of this study was to evaluate the influence of curing mode on bond strength (BS) of three cementing systems to bovine dentin. Methods: The buccal enamel surfaces of 50 bovine incisors were removed to expose dentin and to flat the surface. The teeth were divided into five groups (n=10), which consisted of two resin cements (Multilink and Clearfil SA Cement) that were tested in dual- (halogen light for 40 s) and self-cured modes, and a control (RelyX ARC). Two cylinders of resin cements (1.0 mm X 0.75 mm) were prepared on each bonded dentin surface. After 24h at 37oC, resin cylinders were subjected to micro-shear testing in a universal testing machine (4411/Instron - 0.5 mm/min). Data were statistically analyzed by two-way ANOVA, Tukey and Dunnett`s test (5%). Results: Multilink showed higher BS than those observed on Clearfil SA. Light-curing resulted in higher BS for both Multilink and Clearfil SA. When Multilink was light-cured, no significant difference on BS was demonstrated between it and RelyX ARC. Conclusions: The highest BS values were obtained in control group and light-cured Multilink resin cement.